Mathematical Modelling of the Volumetric Efficiency for Fluted Rolls Metering Different Crop Seeds - Muhammed Hakan Özdemir; Adnan Değirmencioğlu (Turkish Journal of Agriculture: Food Science and Technology)
The objective of this study was to develop a mathematical model for predicting the volumetric efficiency for fluted rolls metering different crop seeds. A special test stand was designed and manufactured in order to conduct experiments in order to find out the volumetric efficiency of the fluted rolls. In order to meet the above objective, alfalfa, barley, coriander, flax, oat, rye, safflower, sesame and wheat seeds were used. Experiments were conducted at different roll revolutions and roll lengths by considering the seed rate for each crop and the rolls were driven by a step motor as controlled by a software installed on a laptop computer. Five replications were achieved for each experiment and a total of 1660 flow rate data was obtained. Five different models for volumetric efficiency were developed. Analysis based on different goodness of fit criteria were achieved to compare models in to order to select the appropriate one. The study conducted not only resulted in developing volumetric efficiency models but also revealed an important finding based on low flow evenness (low CV, %) values obtained as compared to other studies in the literature.